Students Understanding of the Use of Multimeters in Basic Electronics Lab At Sriwijaya State Polytechnic - Dicky Wahyu; Zidni Ma'ruf; Sopa Tarwiyah; Raju Akbar (JUPITER (JURNAL PENDIDIKAN TEKNIK ELEKTRO), 2026)
Multimeters are fundamental measuring instruments in electrical engineering education, used to measure voltage, current, resistance, and other electrical quantities. However, students frequently struggle with their proper use, making errors such as selecting incorrect scales, misidentifying measurement functions, and misreading results. This study examines students’ proficiency in using multimeters during basic electronics laboratory practicals and identifies the factors contributing to measurement errors. The research employs an observational and descriptive method, analyzing student performance during practical sessions in an electrical engineering department. The results indicate that many students lack sufficient mastery of multimeter operation, which negatively impacts the effectiveness of laboratory activities. Practical work plays a crucial role in bridging theoretical concepts with real-world application, and the inability to properly operate measuring instruments undermines this learning objective. Targeted instructional guidance and structured practical modules are recommended to improve students’ measurement competencies. Enhancing multimeter proficiency is essential for optimizing laboratory learning outcomes and developing students’ analytical and practical skills in electrical engineering education